Engaged Humanities Rethinking Art, Culture, and Public Life - Swinnen, Aagje; Kluveld, Amanda; de Waal, Renée (Amsterdam University Press, 2022)
What is the role of the humanities at the start of 21st century? In the last few decades, the various disciplines of the humanities (history, linguistics, literary studies, art history, media studies) have encountered a broad range of challenges, related to the future of print culture, to shifts in funding strategies, and to the changing contours of culture and society. Several publications have addressed these challenges as well as potential responses on a theoretical level. This coedited volume opts for a different strategy and presents accessible case studies that demonstrate what humanities scholars contribute to concrete and pressing social debates about topics including adoption, dementia, hacking, and conservation. These "engaged" forms of humanities research reveal the continued importance of thinking and rethinking the nature of art, culture, and public life.